PERGESERAN KOMPETENSI ABSOLUT DARI PERADILAN UMUM KE PERADILAN TATA USAHA NEGARA: GUGATAN PERBUATAN MELAWAN HUKUM OLEH PENGUASA (ONRECHTMATIGE OVERHEIDSDAAD) - Barokah, Muhamad Raziv; Erliyana, Anna (UI Scholars Hub, 2021)
The absolute competency-shifting in adjudicating a lawsuits against the law by authorities from the general court to the state administration court suddenly based on Supreme Court Regulation No. 2/2019 raises 2 (two) issues regarding differences in the parameters of evaluating government actions in terms of civil law with state administration law and a significant reduction in the time period for filing a lawsuit from 30 (thirty) years to 90 (ninety) days. This research takes the form of a normative juridical approach to the rule of law. This study concludes there are differences in the parameters of the OOD Claims between general and administrative court. PN uses 4 alternative parameters in the form of conflict against 1) law regulation; 2) other people subjective rights; 3) morality; or 4) propiety. Administrative court uses 5 alternative parameters in the form of 1) statutory regulations; 2) General Principle of Good Governance; 3) authority; 4) procedure; or 5) substance. Ideally, the Administrative Court absorbs parameter from the general court